Modeling the behavior of Listeria monocytogenes during enrichment in half Fraser broth; impact of pooling and the duration of enrichment on the detection of L. monocytogenes in food. (December 2016) - Augustin, Jean-Christophe; Kalmokoff, Martin; Ells, Timothy; Favret, Sandra; Desreumaux, Jennifer; Decourseulles Brasseur, Emilie; Gnanou Besse, Nathalie
Abstract: A stochastic model describing the growth of Listeria monocytogenes during enrichment in half Fraser was developed for the purpose of estimating the effects of modifications to the first enrichment step of the EN ISO 11290-1 detection method. Information pertaining to the variability of growth rates, physiological state of the cell, and the behavior of individual cells contaminating the food were obtained from previously published studies. We used this model to investigate the impact of pooling enrichment broths (wet pooling) on the performance of the standard method. For validation of the model, the numbers of L. monocytogenes occurring in 88 naturally contaminated foods following pre-enrichment were compared to model-simulated microbial counts. The model was then used to perform simulations representative of the natural contamination observed for smoked salmon in the European baseline survey of 2010–2011. The model-estimated L. monocytogenes levels following individual enrichment or following the pooling of five broths where only one would be contaminated were compared. The model indicated a 10% loss of method sensitivity resulting from wet pooling. The model also predicted a 5% decrease in the sensitivity of the method when the duration of the enrichment was reduced from 24 to 22 h. Highlights: The stochastic behavior of Listeria monocytogenes during pre-enrichment is modeled. Wet pooling leads to a 10% loss of sensitivity for the detection method. Decreasing the enrichment duration from 24 to 22 h leads to a 5% loss of sensitivity.